Evaluation of Traffic Noise Exposure in Old Folks' Homes, Batu Pahat, Johor - Yean Ghing, Tong (International Journal of Integrated Engineering, 2025)
Excessive noise exposure can adversely affect the elderly, causing sleep disorders, depression, and stroke. To analyze the noise levels in old folks’ homes, this study used a data logging sound level meter to evaluate traffic noise levels of three old folks’ homes located along the busy road of Jalan Kluang during peak hours of weekdays and weekend (7.30am to 9.30am and 4.30pm to 6.30pm). Traffic counts according to different classes were carried out during the first hour of the survey. The study showed that traffic volume did not affect noise levels at Rumah Sejahtera Batu Pahat and Sherun Old Folk Home (BP), but a positive correlation was found at Healthlife Old Folks Home. Noise levels (LAeq(2hrs)) recorded for Rumah Sejahtera Batu Pahat, Sherun Old Folks Homes (BP), and Healthlife Old Folks Homes were 75 dBA, 67 dBA and 70 dBA, respectively. They are all above recommended values set by the Department of Environment Malaysia (DOE) which is 60 dBA for daytime. The noise levels at nearby buildings, including old folks' homes, are likely to be around or exceeding the DOE standard. The research is essential as it evaluates the seriousness of traffic noise pollution around the old folks’ homes along Jalan Kluang. This study will be helpful for future research and development of built-environment plans.